PERAN BIAYA SOSIAL TERHADAP PENINGKATAN KINERJA SOCIAL RESPONSIBILITYPADA PERUSAHAAN INDUSTRI MANUFAKTUR LISTED DIBURSA EFEK INDONESIA - Hadi, Nor (IQTISHADIA, 2017)
This article examining the relationship between social cost (environment, energy, community, employee, and consumen) and social performance in 62 companies representing manufacture industries in Indonesia Stock Exchange. Social cost and social performance were capture from responden are CEO by survey. Data analysis by multivaried regression. Results suggest that legitimacy theory may be an explanatory of social responsibility practice. Statistical testing results enviromental cost are significant related social performance. While, the social cost (environment, energy, employee, and consumen) staistics test result are significant related social performance.